2015
DOI: 10.1016/j.epsl.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mantle carbonatite metasomatism through Os–Sr–Mg isotopes in Tibetan ultrapotassic rocks

Abstract: Mantle-derived magmas at convergent plate boundaries provide unique insights into the nature of materials subducted to and recycled from depths. Here we present a study of OsSrMg isotopes on the Oligocene-Miocene ultrapotassic rocks aimed at better understanding sediment subduction and recycling beneath southern Tibet. New isotopic data confirm that ultrapotassic rocks in southern Tibet are of mantle origin, but underwent crustal contamination as evidenced by the variably high 187 Os/ 188 Os that obviously d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…However, numerous crustal xenoliths and zircon xenocrysts found in the ultrapotassic lavas may indicate significant crustal assimilation (Liu, Zhao, Zhu, Niu, Depaolo, et al, ; Liu, Zhao, Zhu, Niu, & Harrison, ; Miller et al, ). This scenario is consistent with the variably high 187 Os/ 188 Os values of the ultrapotassic lavas that were most likely caused by crustal assimilation (Liu et al, ). Given that the Konglong mafic enclaves likely originated from primary ultrapotassic magmas, they can provide key petrogenetic information concerning the origin and evolution of these magmas.…”
Section: Discussionsupporting
confidence: 84%
“…However, numerous crustal xenoliths and zircon xenocrysts found in the ultrapotassic lavas may indicate significant crustal assimilation (Liu, Zhao, Zhu, Niu, Depaolo, et al, ; Liu, Zhao, Zhu, Niu, & Harrison, ; Miller et al, ). This scenario is consistent with the variably high 187 Os/ 188 Os values of the ultrapotassic lavas that were most likely caused by crustal assimilation (Liu et al, ). Given that the Konglong mafic enclaves likely originated from primary ultrapotassic magmas, they can provide key petrogenetic information concerning the origin and evolution of these magmas.…”
Section: Discussionsupporting
confidence: 84%
“…Several ultrapotassic and potassic volcanic rocks related to the closure of the Tethys Ocean were considered to originate from the recycling of carbonate‐rich sediments within the lithospheric mantle (Ammannati et al, ; Conticelli et al, ; Liu et al, ). Both carbonated metasediments (e.g., carbonate‐bearing mudrocks, δ 26 Mg = −0.74 to −0.08) (Wang et al, ) and sedimentary carbonates (δ 26 Mg = −5.31 to −1.09) (Saenger & Wang, ) have light Mg isotopic composition compared to the upper mantle.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huang et al () combined Ca and Sr isotopes to trace recycled carbonates and proposed that the addition of 4% ancient carbonates into the Hawaiian source could explain the variation of δ 44/40 Ca in Hawaiian shield lavas. D. Liu et al () identified carbonatite metasomatism using Mg–Sr–Os isotopes and suggested that the variably low δ 26 Mg of Tibetan ultrapotassic rocks could be attributed to carbonate‐bearing sediments. Mg–Sr–O isotopes were employed to study the origin of syenites from northwest Xinjiang, China, showing that syenites with low δ 26 Mg were caused by the incorporation of dolostone, limestone, and Indian sediment (Ke et al, ).…”
Section: Discussionmentioning
confidence: 99%